2015
DOI: 10.1111/1750-3841.12917
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and Immunoreactivity of Shrimp Extracts Using an In Vitro Digestibility Model with Pepsin and Pancreatin

Abstract: Unlike other food allergies, shellfish allergy is typically life-long and predominantly affects the adult population. A major difficulty in managing shellfish allergy is the lack of reliable diagnostic assays due to limited knowledge of clinically relevant shellfish allergens. Therefore, the identification and characterization of digestive-stable and immunoreactive food proteins is fundamental to the development of new polyclonal antibodies for improved food allergen detection methods within the food industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Almost the same bands can be seen in all other extracts (except the high pressure steamed sample) although the intensities of the bands were reduced. Prominent protein bands in the extracts from processed samples include 200 kDa (myosin heavy chain), 100 kDa (α-actinin), a 75 kDa band, 42 kDa (arginine kinase), 36 kDa (tropomyosin) and 20 kDa (myosin light chain) (Liu, Huang, Cai, Weng, Su & Cao, 2011, Toomer, Do, Fu & Williams, 2015. In comparison with other bands however, the band intensities of tropomyosin and myosin light chain were enhanced (Fig 1).…”
Section: Sds-page Analysismentioning
confidence: 96%
“…Almost the same bands can be seen in all other extracts (except the high pressure steamed sample) although the intensities of the bands were reduced. Prominent protein bands in the extracts from processed samples include 200 kDa (myosin heavy chain), 100 kDa (α-actinin), a 75 kDa band, 42 kDa (arginine kinase), 36 kDa (tropomyosin) and 20 kDa (myosin light chain) (Liu, Huang, Cai, Weng, Su & Cao, 2011, Toomer, Do, Fu & Williams, 2015. In comparison with other bands however, the band intensities of tropomyosin and myosin light chain were enhanced (Fig 1).…”
Section: Sds-page Analysismentioning
confidence: 96%
“…For example, peach lipid transfer protein, which is the main allergen in peach, is mainly hydrolyzed by trypsin and is resistant to pepsin and chymotrypsin; intact proteins and some high molecular weight peptides can be recognized by the patient's serum (Cavatorta et al, 2010). Toomer et al (2015) conducted a simulated gastric (0.8 U/μg pepsin; pH 2; 37 • C; 60 min), intestinal (32 U/μg pancreatin; pH 7.5; 37 • C; 60 min), and gastrointestinal digestion (60 min of gastric digestion and 30 min intestinal digestion) of total shrimp proteins, which found that only proteins that were stable to pepsin, trypsin, and chymosin simultaneously might trigger an immune response. Since both the stomach and intestine contain digestive enzymes that may hydrolyze allergens, it is also important to further study the changes in digestive characteristics and potential allergenicity of allergens during intestinal digestion.…”
Section: Duodenum Digestionmentioning
confidence: 99%
“…Tropomyosins are alpha-helical coiled-coil proteins that generally exist as a dimer, and show high heat stability and resistance to pepsin digestion. 9,10 Recent studies have demonstrated that structural and fold stability of allergenic proteins have a direct impact on their allergenicity through differential endolysosomal degradation and subsequent generation of allergen-derived peptides for MHC Class II presentation on antigen presenting cells, as shown in the case of Bet v 1, a major birch pollen allergen. 11 Whether structural differences influence allergenicity and cross-reactivity of the various tropomyosins, remains unclear.…”
Section: Introductionmentioning
confidence: 99%